Changes in ovarian structures, blood biochemical and hormonal profile in double Ovsynch treated conceived and non-conceived Jaffarabadi buffaloes - RAVAL, R J; PATBANDHA, T K; TRANGADIA, B J; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Sciences, 2022)
The present study comprised 12 post-pubertal acyclic buffalo heifers (40-50 months of age) and 6 postpartum lactating acyclic buffalo cows. Animals were monitored for ovarian changes by ultrasonography along with blood sampling on different days of hormonal treatment, on day 27 of protocol and on day 12, 21 and 35 post-insemination. Total 10 animals (55.56%; 9/12 heifers; 1/6 buffalo) conceived at fix timed artificial insemination (FTAI) and remaining 8 animals were considered as non-conceived for comparison. Significantly higher number of large follicles was observed on day 7 with reduction in mean diameter of subordinate follicles at day 26, decreased plasma levels of FSH on day 17, 24 and 26; increased plasma level of LH on day 27, with higher insulin level in conceived animals as compared to non-conceived animals. Significant reduction in number of large follicles was recorded on day 21 post- AI in conceived animals. The difference in the levels of progesterone was statistically significant between conceived and non-conceived animals at day 35 post-AI. There were highly significant positive correlations among population of different size follicles, total follicles and largest and subordinate follicles diameter, whereas they had negative correlation with plasma protein and cholesterol both in conceived and non-conceived animals, but their correlations with plasma LH, insulin and estrogen were significant and positive only among non-conceived group.